2020
DOI: 10.1007/s10686-020-09687-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of complete safe coordination of astrobots for Sloan Digital Sky Survey V

Abstract: The data throughput of massive spectroscopic surveys in the course of each observation is directly coordinated with the number of optical fibers which reach their target. In this paper, we evaluate the safety and the performance of the astrobots coordination in SDSS-V by conducting various experimental and simulated tests. We illustrate that our strategy provides a complete coordination condition which depends on the operational characteristics of astrobots, their configurations, and their targets. Namely, a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This strategy successfully yields a completeness condition which can be locally evaluated based on the specifications of astrobots in various states, e.g., their initial and target spots. In particular, it is also formally shown that if all of the neighborhoods are completely coordinated, then the coordination of the whole astrobots swarm associated with those neighborhoods is globally complete [17], [18]. Thus, the nonlinear hybrid control discussed in the previous section is substituted with the paradigm of cooperative nonlinear hybrid (CNH) control as depicted in Figure 5a.…”
Section: B Coordination Controlmentioning
confidence: 99%
“…This strategy successfully yields a completeness condition which can be locally evaluated based on the specifications of astrobots in various states, e.g., their initial and target spots. In particular, it is also formally shown that if all of the neighborhoods are completely coordinated, then the coordination of the whole astrobots swarm associated with those neighborhoods is globally complete [17], [18]. Thus, the nonlinear hybrid control discussed in the previous section is substituted with the paradigm of cooperative nonlinear hybrid (CNH) control as depicted in Figure 5a.…”
Section: B Coordination Controlmentioning
confidence: 99%
“…We wish to predict the success of this path generator without having to run it, which will provide a method for assessments for target selection. This is useful because the complete path generator [6,7] may require some time longer than the available time between two consecutive observations to run, which makes it computationally expensive for path generations. So, we are interested in using those which do not generally fulfill completeness, should they reach a minimum satisfactory convergence rate.…”
Section: Guiding and Focusmentioning
confidence: 99%
“…Thus, reaching a minimum of convergence rate in a swarm is an important requirement. This complicated swarm control problem is already solved using artificial potential fields [6,7,8] and supervisory control [9]. These methods can check the completeness of a typical swarm configuration.…”
Section: Introductionmentioning
confidence: 99%